Development of Nephropathy in Chronic Heart Failure - Orifovna, Djuraeva Nozima (Journal of Innovation in Education and Social Research, 2025)
Chronic heart failure (CHF) is a clinical syndrome characterised by the inability of the heart to provide adequate blood flow to meet the metabolic needs of the body. One of the most significant and frequent complications of CHF is the development of chronic kidney disease (CKD), which together form the so-called cardiorenal syndrome. The relationship between cardiac and renal dysfunction is bidirectional and reflects the complex pathophysiological interdependence of these organs.